2021
DOI: 10.33160/yam.2021.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Why Are COVID-19 Mortality Rates by Country or Region So Different?: An Ecologic Study of Factors Associated with Mortality from Novel Coronavirus Infections by Country

Abstract: Background In order to find out the factors associated with the large disparities in COVID-19 mortality rates by country, we conducted an ecological study by linking existing statistics. In Japan, a large variation was observed in between geographical areas when assessing mortality. We performed a regional correlation analysis to find factors related to regional mortality. Methods This study design was an ecologic study. A multiple regression analysis was performed with COVID-19 mortality rates of different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In this study, a 5.5-fold difference was observed in the COVID-19 mortality index by region. Such differences have also been observed in several regions (22) , (23) , (33) , (34) . For example, a previous study in 30 European countries reported up to 185-fold regional differences in the COVID-19-related deaths among these nations (34) .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In this study, a 5.5-fold difference was observed in the COVID-19 mortality index by region. Such differences have also been observed in several regions (22) , (23) , (33) , (34) . For example, a previous study in 30 European countries reported up to 185-fold regional differences in the COVID-19-related deaths among these nations (34) .…”
Section: Discussionsupporting
confidence: 57%
“…Second, the risk of death among Omicron-positive individuals is known to be age-dependent (43) ; however, in this study, age adjustment could not be performed for the COVID-19 mortality index because the ages of patients who died due to COVID-19 were not publicly available in approximately one-third of the prefectures. Third, factors such as climate and the number of international travelers to Japan are known to be related to COVID-19 mortality (33) , (44) ; however, detailed regional data on these factors were not considered in this study. Fourth, this study analyzed the seventh wave, when Omicron variant BA.5 was predominant (7) ; however, whether similar results will be obtained in future pandemics may depend on the emergence of mutant strains and regional conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10 Within Japan, a large regional disparity in COVID mortality was observed. The ratio of mortality rates in the most and least affected territorial units was 83 to 1 during the first wave of the pandemic (Osaki et al 2021).…”
Section: Getting Around the Black Boxmentioning
confidence: 96%
“…Previous studies tried to describe the regional differences in COVID-19 epidemiology in Japan [ 5 , 6 ]. However, the prefectural differences in terms of mortality have not been well investigated, particularly on the outliers with significantly higher or lower mortality.…”
Section: Notementioning
confidence: 99%